Considérations sur les changements intervenus dans les gestions financières des municipalités durant le processus d’adhésion de la Turquie à l’Union Européenne - Tüǧen, Kamil; Yaşa, Ayse Atilgan (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Local governments, being an important element of the governments of the municipalities are considered the cradle of democracy. It is an important aim for all democratic countries, like EU members to build more democratic and more participant local authorities. Turkey, which takes important steps towards being a member of the EU, has adopted these aims.In EU member states, the significance of municipalities in the structure of public administration is increasing. In EU countries an effort is being made to encourage individuals to participate in the search for solutions to common problems of the place where they live. As the active participation of local people is thought to guarantee the legal regulations, municipalities also benefit from new developments relating to financial management.Turkey, whose candidate position to EU was adopted in 1999 and which started negotiations in 2005 has taken important steps with municipalities towards alignment with the acquis. EU Progress Reports evaluate the steps taken by Turkey and they reveal that the country did what was necessary to do. In our paper the observed changes in financial management of municipalities in EU accession process of Turkey will be evaluated.
Keywords: zarządzanie podatkami (zarządzanie budżetem); przejrzystość podatkowa; autonomia fiskalna; decentralizacja